2019
DOI: 10.24251/hicss.2019.840
|View full text |Cite
|
Sign up to set email alerts
|

Dependency Management in Large-Scale Agile: A Case Study of DevOps Teams

Abstract: Managing dependencies between teams and within teams is critical when running large-scale agile projects. In large-scale software development, work is carried out simultaneously by many developers and development teams. Results are delivered frequently and iteratively, which requires management of dependencies on both the project and team level. This study explores coordination mechanisms in agile DevOps teams in a large-scale project and how the mechanisms address different types of dependencies. We conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Moreover, Calefato and Lanubile [8] proposed a model to integrate developer tools with Slack as a hub. In an earlier study of a large-scale agile project, we found that Slack managed knowledge, processes, and resource dependencies [89]. Coordination on Slack can be categorized as vertical when team members communicate with their manager and horizontal when communicating with their team members.…”
Section: Slack As a Collaboration Tool For Mutual Adjustmentmentioning
confidence: 95%
“…Moreover, Calefato and Lanubile [8] proposed a model to integrate developer tools with Slack as a hub. In an earlier study of a large-scale agile project, we found that Slack managed knowledge, processes, and resource dependencies [89]. Coordination on Slack can be categorized as vertical when team members communicate with their manager and horizontal when communicating with their team members.…”
Section: Slack As a Collaboration Tool For Mutual Adjustmentmentioning
confidence: 95%
“…We believe that our study has the following main implications for PO coordination. First, we recommend focusing more on unscheduled meetings rather than scheduled, time-consuming meetings, as also suggested by other research on large-scale agile [22,28]. Established frameworks such as the Scaled Agile Framework and Large-Scale Scrum recommend a rather fixed meeting structure [16,17].…”
Section: Implications For Practicementioning
confidence: 97%
“…Inter-team coordination is one mechanism for managing dependencies in largescale agile. Dingsøyr et al [6] described 14 inter-team coordination mechanisms in a large-scale software project, while Stray et al [28] identified 20 mechanisms (11 synchronization activities and nine synchronization artifacts). Paasivaara et al [24] found that the product owner (PO) and the PO team were critical in assisting with interteam coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale agile transformation is a critical issue in responding to the digital transformations that are ongoing in many sectors [1]. Several barriers to such transformation seen from industry experience have been identified, for example, change resistance [8], and inter-team coordination challenges [16]. While conceptual solutions such as continuous development and BizDev has been suggested [3], there is a lack of research-based advice on how agile transformations are to be performed in practice.…”
Section: Discussionmentioning
confidence: 99%